Palladium-Catalyzed Stereospecific Coupling of BINOL-bistriflates and Zinc Cyanide and Applications in the Synthesis of 1,1′-Binaphthyl-2,2′-bisoxazolines (BOXAX) - Dong, Zhan; Zhong, Dayou; Li, Zi-Meng; Liu, Wei-Min; Zhao, Jing; Liu, Wen-Bo (Synlett, 2022)
A palladium-catalyzed synthesis of enantiopure [1,1′-binaphthalene]-2,2′-dicarbonitriles from BINOL-bistriflates and zinc cyanide is reported. This cross-coupling reaction employs a 0.1–5 mol% catalyst loading, and is scalable and stereospecific. The synthetic applications of this reaction are demonstrated by product derivatizations and the synthesis of [1,1′-binaphthalene]-2,2′-bisoxazolines (BOXAX).
Keywords: atropchiral compounds; palladium; cyanation; cross-coupling; stereospecific; chiral ligand